Fatty Replacement of Lower Paraspinal Muscles: Normal and Neuromuscular Disorders - Hadar, Herzlia; Gadoth, Natan; Heifetz, Marina (American Journal of Neuroradiology, 1983)
The physiologic replacement of the lower paraspinal muscles by fat was evaluated in 157 patients undergoing computed tomography for reasons unrelated to abnormalities of the locomotor system. Five patients with neuromuscular disorders were similarly evaluated. The changes were graded according to severity at three spinal levels: lower thoracic–upper lumbar, midlumbar, and lumbosacral. The results were analyzed in relation to age and gender. It was found that fatty replacement of paraspinal muscles is a normal age-progressive phenomenon most prominent in females. It progresses down the spine, being most advanced in the lumbosacral region. The severest changes in the five patients with neuromuscular disorders (three with poliomyelitis and two with progressive muscular dystrophy) consisted of complete muscle group replacement by fat. In postpoliomyelitis atrophy, the distribution was typically asymmetriC and sometimes lacked clinical correlation. In muscular dystrophy, fatty replacement was symmetric, showing relative sparing of the psoas and multifidus muscles. In patients with neuromuscular diseases, computed tomography of muscles may be helpful in planning a better rehabilitation regimen.